Cover Image, Volume 29, Issue 12. (December 2016) - Kjølby, B.F.; Khan, A.R.; Chuhutin, A.; Pedersen, L.; Jensen, J.B.; Jakobsen, S.; Zeidler, D.; Sangill, R.; Nyengaard, J.R.; Jespersen, S.N.; Hansen, B.
Abstract : The cover image, by B.F. Kjølby et al., is based on the Research Article Fast diffusion kurtosis imaging of fibrotic mouse kidneys, DOI:10.1002/nbm.3623 .